2017
DOI: 10.1097/gox.0000000000001239
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma Gangrenosum after Deep Inferior Epigastric Perforator Breast Reconstruction: Systematic Review and Case Report

Abstract: Background:Pyoderma gangrenosum (PG) is a rare skin disorder of the neutrophilic dermatoses spectrum that can mimic wound infections in surgical patients. PG after breast surgery has been reported but in limited amounts in autologous breast reconstruction patients. We present the first case of PG after a delayed bilateral deep inferior epigastric perforator flap breast reconstruction in the setting of systemic disease along with a systematic review.Methods:PubMed, Ovid, and Web of Science were systematically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In 2 recent systematic reviews, 18 (86%) of 21 cases of PSPG following breast reconstruction, including DIEP and TRAM flaps, developed donor-site PG. 6,8 Abdominal donor-site involvement was present in our case and aided in recognition and diagnosis of PSPG.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In 2 recent systematic reviews, 18 (86%) of 21 cases of PSPG following breast reconstruction, including DIEP and TRAM flaps, developed donor-site PG. 6,8 Abdominal donor-site involvement was present in our case and aided in recognition and diagnosis of PSPG.…”
Section: Discussionsupporting
confidence: 53%
“…Other research groups have suggested forgoing tissue biopsy and focusing instead on a clinical diagnosis of PG. 8 The consultant dermatologist involved in our patient’s inpatient care was confident in the PG diagnosis despite the equivocal pathology results. Indeed, previous PG diagnostic criteria proposed by Su et al 9 featured major criteria that did not require histopathologic confirmation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Pyoderma gangrenosum after breast reconstruction is a rare complication sparking systematic reviews to illuminate risk factors. [7][8][9] In this report, both patients received adjuvant PMRT, had no prior history of any PG associated conditions, and developed PG involving only the irradiated mastectomy chest wall tissue bed; the donor sites and autologous flaps were spared. Furthermore, Case 2 had bilateral reconstruction and developed PG only on the previously irradiated side; the contralateral reconstructed breast was unaffected.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the role of PMRT in the pathogenesis of PG, current reports and systematic reviews have failed to link the two 5,6 . While many patient factors have been associated with PG, prior radiation therapy is not currently described as a risk factor 2,7‐9,12 . This is despite evidence that radiation exposure fundamentally alters interleukin homeostasis in human tissues, including IL‐8 8,13‐15 .…”
Section: Discussionmentioning
confidence: 99%